Simulation On The Impact Of Cross-Phase Modulation (XPM) On WDM Optical Transmission System - Ezmir Mohd Razali, (2003)
The innovation of Wavelenght Division Multiplexing (WDM) has provided the scalability necessary to cope with the capacity demands of data-driven communications. This technology fully utilizes the huge bandwidth potential offered by fiber by transmitting several wavelenghts or channels inside the same fiber. However, it causes a nonlinear interaction between the co-propagation pulses through a nonlinear phenomenon known as Cross-Phase Modulation (XPM). XPM proved to be a major limiting factor that causes high performance degradation especially for WDM system deploying Intensity Modulation with Direct Detection (IM DD) scheme.